2019
DOI: 10.1021/acs.jpcc.9b02253
|View full text |Cite
|
Sign up to set email alerts
|

Optoelectronic Tunability of Hf-Doped ZnO for Photovoltaic Applications

Abstract: The need for a high optical spectrum throughput, high conductivity, and controlled energy levels of transparent conductive oxide used in solar cells stresses the development of novel materials that help reduce the existing dependency on indium-based oxides. ZnO is a promising material in this context, and in this work, we demonstrate how Hf doping of ZnO films allows engineering both electrical and optical properties to fit the requirements of different solar cell architectures and materials. We focus on the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…)/( ) opt 2 0 e (10) where ε ∞ and ε 0 are the dielectric constants of the medium and free space, respectively, and m e * is the effective mass of the charge carriers. Furthermore, N opt , ρ, and μ, τ exhibit the following relationships: 1/τ = −e/(m e *μ)] and ρ = 1/ (N opt e μ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…)/( ) opt 2 0 e (10) where ε ∞ and ε 0 are the dielectric constants of the medium and free space, respectively, and m e * is the effective mass of the charge carriers. Furthermore, N opt , ρ, and μ, τ exhibit the following relationships: 1/τ = −e/(m e *μ)] and ρ = 1/ (N opt e μ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, ZnO exhibits high chemical stability, good surface uniformity, and a large exciton binding energy of 60 meV. ZnO also has excellent electrical conductivity generated by its high concentration of donor native point defects, such as oxygen vacancies (V O ) and zinc interstitials (Zn i ), enhanced by doping with group IV elements including titanium, 7 zirconium, 8 hafnium, 9,10 and ruthenium. 11 Furthermore, Zr incorporation in ZnO lattice is chemically favorable due to the comparable ionic radii of Zn 2+ and Zr 4+ ions (74 and 73 pm, respectively) for the four-coordinate tetrahedral substitution, which generates two extra electrons by each ionic substitution.…”
Section: Introductionmentioning
confidence: 99%
“…To study the stability of the thin films, the measurements were repeated after 3 weeks and, as can be seen in Figure 6, all electrical properties were improved. This slight enhancement can be attributed to fewer weakly bound oxygen species after the annealing treatments and more deep-level defects passivated with strong bonds [57][58][59][60][61][62].…”
Section: Effect Of Post-annealing In Undoped and Hf-doped Indium Oxid...mentioning
confidence: 99%
“…Electrical properties of Hf-doped transparent conductive thin films prepared by various methods. References [32,34,46,[58][59][60][61][62] have been cited in the Supplementary Materials.…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…Hafnium, being a transition metal that exists in a + 4 oxidation state (charge mismatch: Hf 4+ and Zn 2+ ), a similar ionic radius (0.78 Å) to Zn (0.74 Å), low electronegativity (1.3), and high basicity can be a promising doping candidate to ZnO for self-cleaning applications. Several studies showed that doping with hafnium at a lower concentration can aid in increasing defects (oxygen vacancies) due to charge mismatch and, thus, will aid in producing hydrophilic surfaces. Further, doping with high hafnium concentration will lead to the formation of HfO 2 , which is a strong Lewis base and an efficient suppressor of oxygen vacancy will lead to the development of hydrophobic surfaces. Additionally, strong affinity of hafnium (−1.70 eV) toward oxygen in comparison to that of zinc (−0.76 eV), results in strong bonding between Hf and oxygen ions, thereby leading to a decrease in the concentration of oxygen vacancies.…”
Section: Introductionmentioning
confidence: 99%